DOI: 10.11606/t.42.2010.tde-25032010-150635
|View full text |Cite
|
Sign up to set email alerts
|

O exercício intermitente modula o metabolismo lipídico em ratos: o fígado como órgão gerenciador

Abstract: EDER, R. Intermittent exercise modulates the lipid metabolism in rats: the as the manager. 95 p. Ph.D. Thesis (Biologia Celular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 209 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…submitted to the same diet who did not perform physical activities. Eder (2009) corroborates the results of this study, finding that intermittent training showed an increase in depletion of post-exercise VLDL-TAG and decrease in hepatic deposits of TAG, suggesting higher transport of triacylglyceride to the periphery, seeking to replenish the intramuscular deposits in the post exercise. Garekani et al (2011) points out that the total fat levels in animals with high and moderate levels of exercise are lower compared to sedentary animals, because such alterations also depend on the adaptations the body realizes in the metabolism to meet the energy expenditure during the practice of the exercise.…”
Section: Methodssupporting
confidence: 91%
“…submitted to the same diet who did not perform physical activities. Eder (2009) corroborates the results of this study, finding that intermittent training showed an increase in depletion of post-exercise VLDL-TAG and decrease in hepatic deposits of TAG, suggesting higher transport of triacylglyceride to the periphery, seeking to replenish the intramuscular deposits in the post exercise. Garekani et al (2011) points out that the total fat levels in animals with high and moderate levels of exercise are lower compared to sedentary animals, because such alterations also depend on the adaptations the body realizes in the metabolism to meet the energy expenditure during the practice of the exercise.…”
Section: Methodssupporting
confidence: 91%